(untitled) (Journal of the College of Basic Education, 2022)
Objectives:-A descriptive study was carried out to assess the physiological changes and health behaviors of middle age women Material and Methods:-A purposive samples of (100) married women with age group between (45 – 65) years , data were collected through personal interview by using questionnaire form constructed for the purpose of the study Results:-The results of the study showed that the highest percentage 35% of the study sample was at age (55 – 59) years , 25% of them intermediate graduate , more than half of them were house wives , with high gravidity and parity , 81% of them on previous history for abortion , 67% of them their menstrual cycle cessation and 24% of them their menstrual cycle was irregular .The majority of study sample suffered from menopausal symptoms, and the most symptoms were ( irritability , urinary and sexual problems , joint and muscular discomfort , anxiety , physical and mental exhaustion , hot flushes and sweating , depressive mood and heart discomfort).